2012
DOI: 10.1037/a0028134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normative and diagnosed dissociation on attachment to companion animals and stuffed animals.

Abstract: Companion animals can serve as sources of love and attachment during times of stress. Stuffed animals, too, can provide comfort and stability. However, little research has examined companion animal attachment in highly dissociative trauma survivors, and no studies have systematically assessed stuffed animal attachment in dissociative adults. College student samples with either high or low dissociation levels and a sample of women with dissociative identity disorder (DID) completed questionnaires about attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Similarly, people with an impaired capacity for intimacy with other human beings are at risk for lack of human social support (Beck & Katcher, 2003). In line with these ideas, high attachment to pets has been associated with high scores on the dissociation index (Barlow, Cromer, Caron, & Freyd, 2012;Brown & Katcher, 2001)-with dissociative disorders often associated with an impaired capacity for intimacy with people.…”
Section: Health Consequences Associated With the Presence Of Animalsmentioning
confidence: 91%
“…Similarly, people with an impaired capacity for intimacy with other human beings are at risk for lack of human social support (Beck & Katcher, 2003). In line with these ideas, high attachment to pets has been associated with high scores on the dissociation index (Barlow, Cromer, Caron, & Freyd, 2012;Brown & Katcher, 2001)-with dissociative disorders often associated with an impaired capacity for intimacy with people.…”
Section: Health Consequences Associated With the Presence Of Animalsmentioning
confidence: 91%
“…Dabei können Kuscheltiere auch auf Erwachsene beruhigend wirken, z. B. bei Traumatisierung (Barlow et al 2012). Liebespuppen im Bett würden zwar weniger infantil, dafür befremdlich und pervers anmuten.…”
unclassified
“…Similarly, several studies of adults have evaluated the relationship between companion animal attachment strength and experiences of dissociation, defined as “a separation between processes that are normally integrated, such as events, emotions, and memories,” which may result from severe trauma (especially childhood abuse) 53. For example, a study of college students by Brown and Katcher found that the adult subjects’ levels of dissociation were positively correlated to their attachments to companion animals 54.…”
Section: Human–pet Attachmentmentioning
confidence: 99%
“…The results of a study by Barlow et al supported that finding, with two groups of college students identified as having low versus high levels of dissociation; they also found that a separate sample of women with clinically diagnosed dissociative identity disorder (DID), a condition where an individual presents with two or more distinct personality states or identities, had significantly stronger attachments to companion animals than both of the groups of college students, as measured by the Pet Attachment and Life Impact Scale (PALS). No men with DID took part in the study 53. Assuming that dissociation and DID may be associated with childhood abuse, the evidence suggests that adults who experienced abuse as children may be more likely to develop stronger attachments to companion animals, possibly as a result of unmet needs they had as children for healthy relationships with humans.…”
Section: Human–pet Attachmentmentioning
confidence: 99%